Ethics interventions for healthcare professionals and students: A systematic review - Stolt, Minna (Nursing ethics, 2018)
Background:The ethics and value bases in healthcare are widely acknowledged. There is a need to improve and raise awareness of ethics in complex systems and in line with competing needs, different stakeholders and patients’ rights. Evidence-based strategies and interventions for the development of procedures and practice have been used to improve care and services. However, it is not known whether and to what extent ethics can be developed using interventions.Objectives:To examine ethics interventions conducted on healthcare professionals and healthcare students to achieve ethics-related outcomes.Research design:A systematic review.Methods:Five electronic databases were searched: CINAHL, the Cochrane Library, Philosopher’s Index, PubMed and PsycINFO. We searched for published articles written in English without a time limit using the keywords: ethic* OR moral* AND intervention OR program OR pre-post OR quasi-experimental OR rct OR experimental AND nurse OR nursing OR health care. In the four-phased retrieval process, 23 full texts out of 4675 citations were included in the review. Data were analysed using conventional content analysis.Ethical consideration:This systematic review was conducted following good scientific practice in every phase.Findings:It is possible to affect the ethics of healthcare practices through professionals and students. All the interventions were educational in type. Many of the interventions were related to the ethical or moral sensitivity of the professionals, such as moral courage and empowerment. A few of the interventions focused on identifying ethical problems or research ethics.Conclusion:Patient-related outcomes followed by organisational outcomes can be improved by ethics interventions targeting professionals. Such outcomes are promising in developing ethical safety for healthcare patients and professionals.